Intravascular Crawling of Patrolling Monocytes: A Lèvy-Like Motility for Unique Search Functions? - Moreno-Cañadas, Rocío; Luque-Martín, Laura; Arroyo, Alicia G. (Frontiers in Immunology, 2021)
Patrolling monocytes (PMo) are the organism's preeminent intravascular guardians by their continuous search of damaged endothelial cells and harmful microparticles for their removal and to restore homeostasis. This surveillance is accomplished by PMo crawling on the apical side of the endothelium through regulated interactions of integrins and chemokine receptors with their endothelial ligands. We propose that the search mode governs the intravascular motility of PMo in vivo in a similar way to T cells looking for antigen in tissues. Signs of damage to the luminal side of the endothelium (local death, oxidized LDL, amyloid deposits, tumor cells, pathogens, abnormal red cells, etc) will change the diffusive random towards a Lèvy-like crawling enhancing their recognition and clearance by PMo damage receptors as the integrin αMβ2 and CD36. This new perspective can help identifying new actors to promote unique PMo intravascular actions aimed at maintaining endothelial fitness and combating harmful microparticles involved in diseases as lung metastasis, Alzheimer's angiopathy, vaso-occlusive disorders, and sepsis.